PERFORMANS PRODUKSI DAN REPRODUKSI TERNAK BABI LOKAL DI KODYA KUPANG - Redempta Wea (Politeknik Pertanian Negeri Kupang, 2009)
Performans Production and Local Pig Livestock Reproduction At Kodya Kupang. This study was conducted to asses database about production and reproduction performance of local pig at Kota Kupang (Kelapa Lima and Alak Sub Districs). The method used in this study was survey with direct interview to 60 respondents and direct field observation. Thirty respondents each representing of the District. The variable being measured were production and reproduction performance of local pig. The results showed that production and reproduction performance of local pig at Kodya Kupang still low. The production performance were average birth weight 0,65 kg; average weaning weight 12,5 kg; average dailygain unknown and the reproduction performance were sex ratio 58,35% unknown and 1:1 41,65%; litter index 1-2 times of year, farrowing interval 6-12 months or average 9 months, average litter size 6 head, castration 63,35%, weaning ages 3-7 months or average 5 months, number of weaning unknown, and mortaliy 62,07% in pre weaning periods. Keywords: Production Performance, Reproduction Performance, Local Pig